Ring Stabil Berhingga - Arifin, Samsul (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2013)
In this paper, we will discuss about the characterization of stably finite rings and their properties. We will also discuss about right strong stably finite rings and their relationship, and also its characterization.